2021
DOI: 10.31577/sp.2021.02.822
|View full text |Cite
|
Sign up to set email alerts
|

Mindware Instantiation as a Predictor of Logical Intuitions in Cognitive Reflection Test

Abstract: Following the growing body of evidence suggesting that substantial individual differences in reasoning exist already at the early stages of the reasoning process and that reasoners might be able to produce logical intuitions, the model of mindware automatization posits that the mindware acquired to the extent that it is fully automatized can cue the logically correct type 1 response. We asked 908 participants to solve the Cognitive Reflection Test presented under the two-response paradigm, to obtain both intui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
(113 reference statements)
1
4
0
1
Order By: Relevance
“…Hence, even people who give the alleged system 1 response seem to be processing the alleged system 2 response. Critically, this conflict sensitivity is also observed when potential system 2 processing is knocked out with experimental constraint manipulations (e.g., , 2019bBiałek & De Neys, 2017;Burič & Konrádová, 2021;Burič & Šrol, 2020;Johnson, Tubau, & De Neys, 2016;Pennycook, Trippas, Handley, & Thompson, 2014;. In line with the two-response findings, this indicates that the alleged unique system 2 response is also being processed intuitively.…”
Section: Empirical Evidencesupporting
confidence: 65%
See 1 more Smart Citation
“…Hence, even people who give the alleged system 1 response seem to be processing the alleged system 2 response. Critically, this conflict sensitivity is also observed when potential system 2 processing is knocked out with experimental constraint manipulations (e.g., , 2019bBiałek & De Neys, 2017;Burič & Konrádová, 2021;Burič & Šrol, 2020;Johnson, Tubau, & De Neys, 2016;Pennycook, Trippas, Handley, & Thompson, 2014;. In line with the two-response findings, this indicates that the alleged unique system 2 response is also being processed intuitively.…”
Section: Empirical Evidencesupporting
confidence: 65%
“…However, two-response studies with these and other classic bias tasks have shown that this is typically not the case. Those reasoners who give the correct response as their final response after deliberation often already generate this same correct response at the initial, intuitive response stage (e.g., , 2019aBurič & Konrádová, 2021;Burič & Šrol, 2020;Dujmović, Valerjev, & Bajšanski, 2021;Raoelison et al, 2020;. Hence, sound reasoners do not need to deliberate to correct an initial response, their initial response is already correct.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Hence, even people who give the alleged system 1 response seem to be processing the alleged system 2 response. Critically, this conflict sensitivity is also observed when potential system 2 processing is knocked out with experimental constraint manipulations (e.g., Bago & De Neys, 2017, 2019b; Białek & De Neys, 2017; Burič & Konrádová, 2021; Burič & Šrol, 2020; Johnson, Tubau, & De Neys, 2016; Pennycook, Trippas, Handley, & Thompson, 2014; Thompson & Johnson, 2014). In line with the two-response findings, this indicates that the alleged unique system 2 response is also being processed intuitively.…”
Section: Exclusivity In Dual-process Modelsmentioning
confidence: 92%
“…However, two-response studies with these and other classic bias tasks have shown that this is typically not the case. Those reasoners who give the correct response as their final response after deliberation often already generate this same correct response at the initial, intuitive response stage (e.g., Bago & De Neys, 2017, 2019a; Burič & Konrádová, 2021; Burič & Šrol, 2020; Dujmović, Valerjev, & Bajšanski, 2021; Raoelison et al, 2020; Thompson & Johnson, 2014). Hence, sound reasoners do not need to deliberate to correct an initial response, their initial response is already correct.…”
Section: Exclusivity In Dual-process Modelsmentioning
confidence: 99%
“…Recently, researchers have challenged this view, claiming that reasoning based upon logical principles can, in fact, occur at a fast and intuitive level of processing. For example, experiments aimed at knocking out Type 2 processing with time constraints (Pennycook, Trippas, Handley, & Thompson, 2014; Thompson & Johnson, 2014) cognitive load (Franssens & De Neys, 2009; Johnson, Tubau, & De Neys, 2016) or both (Bago & De Neys, 2017) have shown that sensitivity to conflict and correct normative responses can occur at the intuitive stage of processing (Burič & Konrádová 2021; Burič & Šrol, 2020). Dual process 2.0 models (De Neys, 2018; De Neys & Pennycook, 2019) claim that belief‐based and logic‐based responses are activated intuitively and in parallel, leading to the detection of conflict that may or may not be resolved through the intervention of Type 2 deliberative processes (e.g., Bago & De Neys, 2017; De Neys, 2012; Handley & Trippas, 2015).…”
Section: Introductionmentioning
confidence: 99%